ANALISIS KERUSAKAN STICK CYLINDER EXCAVATOR 390F CATERPILLAR - Nuhgraha, Yoddy Agung; Rahmadi, Rizki Dwi (Jurnal TEDC, 2024)
Based on the fact findings in the field, the author found a problem that occurred in the Caterpillar 390F Excavator Stick Cylinder where it was damaged, this damage can be coused by many factors that are suspected to be the cause of the damage that occurred to the stick cylinder. Alleged causes of damage to the stick cylinder include contaminants in hydraulic oil, infrequent maintenance and excessive loads. To find out the main cause of damage that occurs to the stick cylinder, an analysis is carried out using the AFA method which refers to field facts, visuals, and literature studies. Through the analysis process, the possibility of damage was found, namely internal leakage in the stick cylinder, damage to the piston ring and seal, bending of the rod cylinder. Damage to the stick cylinder is caused by damage to the ring (173-3414), ring (155-9157) and seal as (8C-9182) which then causes stick cylinder drift. After analysis, the possibility of part damage is caused by dieseling. Dieseling is caused by air and other gas content that is saturated mixed with oil vapours from hydraulic oil. Its Prevention by removing all air content and flammable gases in the cylinder before use. Move of the cylinder several times up and down, to push the air back into the tank before use.